2019
DOI: 10.1016/j.jmatprotec.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

An application of differential injection to fabricate functionally graded Ti-Nb alloys using DED-CLAD® process

Abstract: The aim of this paper is twofold: firstly, to compare the microstructural and the mechanical properties of Ti-44Nb samples manufactured pre-alloyed powder and differential injection, and secondly, to demonstrate the feasibility of the differential injection method included in the DED-CLAD ® process, to manufacture functionally graded Ti-Nb alloys. Functionally graded materials (FGM) are promising new materials which are perfectly adapted to custom-made parts with various properties for specific applications. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…Using X-ray diffraction patterns, the phases present in similar additively manufactured Ti-xNb alloys were identified in a previous paper for various chemical compositions [34]. It was shown that the Ti deposition consisted of a hexagonal α'-phase formed by the rapid cooling of columnar beta grains, and that when Nb content is ramped up to 25%, the high-temperature bcc β-phase was entirely retained.…”
Section: Comparison Of Young's Modulus Depending On the Characterizatmentioning
confidence: 99%
“…Using X-ray diffraction patterns, the phases present in similar additively manufactured Ti-xNb alloys were identified in a previous paper for various chemical compositions [34]. It was shown that the Ti deposition consisted of a hexagonal α'-phase formed by the rapid cooling of columnar beta grains, and that when Nb content is ramped up to 25%, the high-temperature bcc β-phase was entirely retained.…”
Section: Comparison Of Young's Modulus Depending On the Characterizatmentioning
confidence: 99%
“…The microstructure features of the different graded materials in their as-deposited states has been detailed previously [34,35]. The main features are just recalled in Figure 1b,c for the sake of clarity.…”
Section: Evolution Of the Microstructure Along The Gradientmentioning
confidence: 99%
“…The powders and manufacturing data (power, speed, pitch, etc.) of the samples have been detailed in the works of Schneider et al [34,35]. The FGM walls were cut into 1.5 mm thick slices.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations